Analisis Pemberdayaan Masyarakat Home Industry Dalam Rangka Mendorong Kemandirian Ekonomi - Muhamad Rifai; Warter Agustim; Poppy Indrihastuti (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2015)
Shoots is one type of foodstuffs from young shoots of bamboo plants are quite popular in the community. The young shoots can be consumed, thus classified into vegetable. The main ingredient in the crude bamboo shoot is water, which is about 91%. In addition, bamboo shoots contain protein, carbohydrates, fat, vitamin A, thiamin, riboflavin, vitamin C, as well as other minerals for instance calcium, phosphorus, iron, and calcium. This shoots is often processed into a variety of materials snacks. One of them is the spring rolls bamboo shoots. Spring rolls bamboo shoots business is generally carried out by SME entrepreneurs in many areas in Indonesia, one of which is done by MSMEs in Desa Pakis, Kabupaten Malang. This study aims to look at the extent to which the development of this business in the Desa Pakis, Kabupaten Malang and explore the factors that hinder the development of its business and give suggestions so that this business can be developed further in the future. The findings concerning the factors inhibiting the development of this business, among others, are a product of spring rolls bamboo shoots produced is not hygienic, not durable, not registered at the Malang District Health Office, sales are made to the model consignment with the scope of the marketing area is still very limited, the product packaging is not interestingly, the business has not been registered in the Malang District Industry and Trade Office and difficulty in obtaining loans from banks additional capital for business development.